Предмет: Алгебра,
автор: LizaLolya
(143a^4b^2-9a^3b-11a^3)-(262a^4b^2-a^3d-4a^3)+(119a^4b^2-20a^3+8a^3b)
Ответы
Автор ответа:
0
(143a⁴b² - 9a³b - 11a³) - (262a⁴b² - a³b - 4a³) + (119a⁴b² - 20a³ + 8 a³b) =
= 143a⁴b² - 9a³b - 11a³ - 262a⁴b² + a³b + 4a³ + 119a⁴b² - 20a³ + 8a³b =
= - 27a³
= 143a⁴b² - 9a³b - 11a³ - 262a⁴b² + a³b + 4a³ + 119a⁴b² - 20a³ + 8a³b =
= - 27a³
Похожие вопросы
Предмет: Математика,
автор: hramovjarik061
Предмет: Математика,
автор: maryamiskenderova
Предмет: Английский язык,
автор: rzk98210
Предмет: Математика,
автор: lenaclenina
Предмет: Математика,
автор: nara051282